CHALLENGING CATARACT SURGERY IN VITRECTOMIZED EYES - COMPARING THE SURGICAL OUTCOMES OF FEMTOSECOND LASER ASSISTED CATARACT SURGERY VERSUS CONVENTIONAL PHACOEMULSIFICATION SURGERY: A SYSTEMATIC REVIEW - Gita Noor Azizah; Erlin Prawita Sari; Putty Nabilla; Arsil Abdan (The International Journal of Medical Science and Health Research, 2026)
Introduction: Cataract formation is the most common long-term complication after vitrectomy, and cataract surgery in vitrectomized eyes is technically challenging because of altered ocular anatomy and increased risk of complications. Femtosecond laser-assisted cataract surgery (FLACS) may improve surgical precision and reduce intraoperative trauma compared with conventional phacoemulsification surgery (CPS). This systematic review compared the surgical outcomes of FLACS and CPS in vitrectomized eyes. Method: A systematic review was conducted according to the PRISMA 2020 guidelines. PubMed, Cochrane Library and Science Direct were searched for RCTs, Clinical Trial , and observational studies involving adults (≥18 years) with previous vitrectomy undergoing FLACS or CPS. We assessed risk of bias using RoB 2.0 and ROBINS-I. Our outcomes were the visual acuity, ultrasound energy, Endothelial Cell Condition, surgery time, intraoperative and postoperative complication. Results: We included 4 studies. Visual acuity improved in both groups, with comparable final corrected distance visual acuity. FLACS consistently reduced ultrasound energy requirements, cumulative dissipated energy and operative time. Higher postoperative endothelial cell density and lower endothelial cell loss were also reported with FLACS. Intraoperative complications, including posterior capsule rupture, dropped nucleus, anterior capsule tear, zonular dialysis, and silicone oil migration, occurred predominantly in the CPS group, whereas FLACS-related events were mainly limited to incomplete capsulotomy. Early postoperative corneal edema was less frequent with FLACS, while rates of cystoid macular edema, posterior capsule opacification, and anterior chamber inflammation were generally comparable. Conclusion: FLACS provides superior intraoperative efficiency, better endothelial preservation, faster early visual recovery and a favorable safety profile compared with CPS in vitrectomized eyes, although final visual outcomes remain similar. Larger high-quality randomized studies are required to confirm these findings.